In Defense of Good Work: Jobs, Violence, and the Ethical Dimension - Arenas, Alberto (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. The writer examines the idea that professional ethics are important, but are insufficient for evoking the broader “reverence for life” needed to deal with the current social and environmental malaise. He assesses the belief that in the name of self-interest, technique, or efficiency, any production method or its outcome is acceptable. He highlights the difficult options that poor people face when deciding between self-preservation and self-actualization.